Analysis of Poverty Levels and Economic Growth in Indonesia From An Islamic Perspective - Dini Syafa'ati; Hendri Hermawan Adinugraha (Al-Muamalah: Jurnal Ekonomi Islam, Filantropi dan Perbankan Syariah, 2024)
Poverty represents a multifaceted social issue that has long garnered governmental attention across nations, influenced by factors such as sluggish economic growth, inadequate incomes, limited educational attainment, and escalating unemployment rates. Economic growth is an economic activity that can increase people's income over a certain period of time. Economic growth is not only concentrated on the sale of goods and services but remains focused on the development of high-quality human resources for secular and ukhrawi purposes. This study endeavors to scrutinize poverty and economic growth levels in Indonesia through an Islamic lens. Employing a quantitative methodology, the research draws upon secondary data sourced from diverse outlets including journals, articles, books, research reports, and other written materials. The discoveries uncover that financial development applies negligible impact on destitution levels in Indonesia. Therefore economic growth must be able to reach the poor in a way that governments carry out development that focuses on income distribution.